PERAN BIG DATA DAN SKEPTISISME PROFESIONAL DALAM PENGUMPULAN BUKTI AUDIT - Wibowo, Ezra Ariella; Ardini, Lilis (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2024)
This study was created with the aim of exploring the relationship and relevance between big data, professional skepticism, and audit evidence. With the growing relevance of big data in the world of auditing, the researcher felt the need to observe how big data brings changes in the process of collecting audit evidence, along with the relevance of professional skepticism, which is one of the foundations and essential traits for an auditor, and its relation to the relationship between big data and audit evidence. This research is conducted entirely through literature study and rational argumentation, where the literature used consists of 9 literatures, which consist of books, national and international journals, as well as articles taken from the internet. From this research, it was found that both big data and professional skepticism have significant links to both audit evidence, and to each other